ANALISIS TERJEMAHAN EKSPRESI SOLIDARITAS DAN KEBERPIHAKAN DALAM TEKS KONFERENSI PERS DAN SIARAN MEDIA TENTANG EKSEKUSI NARAPIDANA (PENDEKATAN TEORI APPRAISAL) - Alifa Hanifati Irlinda; Riyadi Santosa; Diah Kristina (Universitas Sebelas Maret, 2016)
Background: This study aims to explain the way appraisal resources in the political text are mediated in the translation. The exploitation of appraisal resources in the source text would determine the pattern used by text speakers in realizing text’s purposes while anticipating and controlling the effect after these purposes are achieved. Furthermore, these evaluations are translated using various translation techniques, which would determine the quality as well as translators’ interference and distortion in balancing the text’s purposes and its aftermath. Methods: This descriptive qualitative study include the source of data that are four transcripts of press conference and media release from Australian government regarding Chan and Sukumaran’s executions in English, and the translation in Bahasa Indonesia. There are 349 data of appraisal resources divided into solidarity and alignment expressions, selected through purposive sampling. Data were then classified into the respective appraisal categories, identified by the translation techniques, and analyzed to find the relation with the translation quality.Results: Majority of translation techniques used in solidarity expressions are Established Equivalent, Borrowing, and Literal that keep most of appraisal categories equivalent to those in the source text; while in alignment expressions are Established Equivalent, Reduction, and Modulation resulting in more deviations in the target text.Conclusion: Interference and distortion are used by translators, consciously or not, to realize text’s goals while minimizing the aftermaths of negative evaluations. Keywords: appraisal, translation technique, translation quality, solidarity, alignment, interference, distortion